Civic Capital and the Vertical Integration of Service Provision: Evidence from Italy - Matthias Buerker; Gaetano Alfredo Minerva (European Regional Science Association (ERSA), 2013)
This paper studies whether civic capital acts an effective restraint against opportunistic behavior in transactions, looking at the degree of outsourcing to external suppliers of service provision in Italian firms. Our results show that, on average, firms tend to outsource more services where civic capital is higher. Two qualifications apply: the firms that are more heavily influenced are the smaller ones; the effect is particularly pronounced in provinces where formal contract enforcement is more difficult. To address the issue of endogeneity we also instrument the current stock of civic capital by historical variables. We argue that the rise in the propensity to engage in transactions with outside service suppliers is evidence of a decrease in the opportunistic behavior between the parties involved in the transaction.
Keywords: Z13; L20; A13; 330